Efeito do paratormônio associado ao uso de biomateriais no crescimento ósseo vertical guiado: estudo pré-clínico em calvária de ratos - Begnini, Gilmar José (2018)
The search for therapies that target vertical bone growth in the reconstruction of the maxillaries includes the use of surgical guides, grafting materials, associated to the use of carriers and hormones. The objective of this study was: 1) to describe a simplified and easy-to-make resin cap for vertical bone growth in calvaria of rats and 2) to evaluate the local and systemic effect of the parathyroid hormone (PTH) associated with the use of biomaterials of bovine or synthetic origin in vertical bone growth in calvaries of rats through histological and histomorphometric analysis. To reach the first objective were made 14 resin caps using acrylic resin inserted in plastic capsules of medicines. In the calvaria of 14 rats two defects of 5 mm in diameter (defect A and defect B) were performed. The defect A served as a donor area of the autogenous bone, which was particulate and filled with defect B, which was covered with the resin cap that served as a guide for vertical bone growth. These animals were subdivided into two subgroups for euthanasia at 15 and 60 postoperative days. The results were analyzed by histology in which it revealed the presence of neoformed bone tissue by almost all the internal space of the resin cap in both experimental periods. To achieve the second objective, 28 male rats were randomly divided into 4 groups: B group (Bio-Oss®), B_PTH group (Bio-Oss® with PTH), N group (Nanosynt®) and N_PTH group (Nanosynt® with PTH) (n = 7). In calvaria of the animals, two bone defects were created in a circular slit shape with a diameter of 5mm with five decorticalized sites. Circular bone crevices were used to fit acrylic resin caps (5 mm in diameter, 3 mm in height and 0.2 mm in thickness), filled with biomaterials, associated or not with PTH. In Group B, the inner of the resin cap was filled only with Bio-Oss®; in Group B_PTH, the inner of the resin cap was filled with Bio-Oss® soaked with 20 μg PTH; in Group N the inner of the resin cap was filled only with Nanosynt®; in Group N_PTH, the inner of the resin cap was filled with Nanosynt® soaked with 20 μg PTH. In the animals of the Groups B_PTH and Groups N_PTH, systemic applications were done subcutaneously of PTH at a dose of 20 μg every 10 days until the euthanasia period. The animals of Groups B and N received, in the same way and for the same period, injections of saline solution. Euthanasia was performed at 15 and 60 postoperative days. Histological and histomorphometric analyzes were performed. The data were submitted to statistical analysis (two-way ANOVA test with Tukey post test) with a significance level of 0.05. At 15 days, in all groups, remaining biomaterial particles were observed permeated by fibrous connective tissue and immature bone neoformation. The B group showed the highest amount of biomaterial remaining (2.75 ± 0.74), in relation to the other groups, B_PTH group (1.58 ± 0.36), N group (1.54 ± 0, 73), N_PTH group(1.31 ± 0.51). There was no difference in the amount of neoformed bone between the groups. At 60 days, in all groups, the new bone formation was mature and permeated the biomaterial particles and connective tissue from the base of the defect following the internal walls of the resin cap until filling almost the entire space. Resin caps kept the material inside and wound healing isolated from adjacent tissues. There was no difference in the amount of remaining biomaterial and neoformed bone between the groups. It is concluded that the resin caps idealized in this study are simple and economical, biotolerable to the tissues adjacent to the surgical field, with precise fitting to the bone groove and that vertical bone growth is possible to be achieved with this methodology and both the researched biomaterials can be considered as choices for these procedures. The non-intermittent use of PTH, at the periodicity of ten days, does not seem to generate benefits to graft and bone neoformation.